(untitled) (El-Wahat Journal for Research and Studies, 2025)
This study seeks to investigate the implications of the temporal and spatial elements apparent to be used in the contents and televised advertising messages and their persuasive roles in promoting Algerian tourism, especially since the advertising industry in Algeria no longer focuses on promoting products only, but that in the compositions of its structure many ideas, values and symbols seeking to achieve several goals, the most prominent of which may be the contribution to the definition of the elements and tourism and cultural potential enjoyed by Algeria, and this in order to involve viewers accurate detailed information that increases their knowledge and raise their conviction to visit those tourist destinations focused on them in various advertising shots. Key words: Temporal and Spatial Embodiments, Persuasion, Television Advertisements, Algerian Tourism.